The locomotor system as seen in Brazilian scientific journals: a mini review (Clinics, 2010)
OBJECTIVE: To make recent selected publications on the locomotor system available to the readership of Clinics. METHOD: A general survey of articles published in selected Brazilian journals was inspected and 91 articles were critically analyzed. They were categorized and briefly described. A final summary of themes is reproduced here. RESULTS: Papers fall into two main categories: articular and muscular pathology and therapeutics; medical sports. A number of papers are not classifiable under these headings. CONCLUSION: The locomotor system has been extensively analyzed and discussed in the Brazilian scientific press in recent years. Not surprisingly, knee and ankle pathology, soccer and running are dominant themes.